Strata Norma Dalam “Karya Cipta Puisi Anak” Karya Murid SDN Banyudono 2 - Amalia, Liza Rizqi; Qomariyah, U'um (UPA Bahasa Universitas Tidar And HISKI Kedu, 2024)
Research on children's literature is still rare because children's literature is not given enough attention. Whereas through children's literature it can increase children's imagination which affects the development of children's abilities. The purpose of this study is to analyze five poems by elementary school children using Roman Ingarden's norm strata approach. This research uses descriptive qualitative method with text analysis. The data source is the poetry collection book